New evidence on nutrition-sensitive agricultural programs - Ruel, Marie T. (International Food Policy Research Institute, 2019)
This chapter summarizes key findings from recent reviews of evidence of the nutritional impacts of agricultural programs. It focuses on findings from impact evaluations of different types of nutrition-sensitive agricultural programs, including biofortification, homestead food production systems, livestock transfer programs, value chains for nutritious foods, and irrigation programs. The review also includes, where available, information regarding pathways of impacts, mechanisms, and contextual factors that affect where and how agriculture may improve nutrition outcomes. The chapter concludes with a discussion of what the findings imply for the design and implementation of successful nutrition-sensitive agricultural programs, and highlights some key research gaps that need to be addressed in order to further our understanding of how to unleash the potential of agriculture to deliver on nutrition.